Spare No Scrap: A Piece of Binder’s Waste as Evidence for Institutional Development at the Abbey of Prémontré in the Thirteenth Century - Wacha, Heather (Revue d'histoire ecclésiastique, 2021)
This article analyses the front flyleaf of the cartulary of Tinselve, a manuscript created at the northern French abbey of Prémontré in the mid-13th century. While the manuscript proper contains acts associated with one of Prémontré’s dependent curtes, Tinselve, the scrap piece of parchment used to create the flyleaf contains brief summaries of five letters to be sent from the abbey to other Premonstratensian houses in France and Germany and to a count of Holland. It is therefore a unique survival of the administrative ephemera which the mother abbey of a major medieval monastic order must once have created in abundance. The authors argue that the Tinselve flyleaf, when viewed within the context of other documents of practice produced at Prémontré, complicates traditional narratives of the Premonstratensian Order’s early years. Rather than supporting a story of harmony among the early followers of Norbert of Xanten, the order’s founder, the flyleaf instead helps us to glimpse the institutional workings of Prémontré and its affiliated communities at a moment in the mid-13th century when its abbots were working hard to assert their primacy over other houses and to implement internal reforms.